2019
DOI: 10.1002/jmri.26617
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of blood oxygen level‐dependent imaging and diffusion‐weighted imaging in early diagnosis of acute kidney injury in animal models

Abstract: Background Early diagnosis of acute kidney injury (AKI) has clinical importance. Current methods are neither adequately sensitive nor specific. Blood oxygen level‐dependent (BOLD) imaging and diffusion‐weighted imaging (DWI) may help to assess AKI in the early phase. Purpose To investigate the feasibility of BOLD imaging and DWI in the assessment of AKI and compare the sensitivities of both techniques in early detection of renal damage. Study Type Prospective animal study. Animal Model Thirty New Zealand white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…Differences of dR2' were found when absolute R2' values were still similar in different severities of AKI, which indicates the advantage of dR2' in sensitivity. Similar with our previous reports (8), the ADC values were also different in control and AKI groups and could not distinguish between different AKI stages effectively in the present study.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Differences of dR2' were found when absolute R2' values were still similar in different severities of AKI, which indicates the advantage of dR2' in sensitivity. Similar with our previous reports (8), the ADC values were also different in control and AKI groups and could not distinguish between different AKI stages effectively in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…Animal experiments were conducted following the guidelines and approval of the institutional animal protection committee (J201740). The model establishement methods were similar as previously reported (8). Twenty New Zealand white rabbits (male, weight range: 2.5-3.5 kg) were randomly divided into mild, moderate, and severe AKI groups and control groups, with five rabbits in each group.…”
Section: Animal Studymentioning
confidence: 99%
See 1 more Smart Citation
“…BOLD MRI is effective in evaluating changes with pharmacological or physiological manipulations, including furosemide, water load, and vasoactive substances [ 92 , 93 ]. Additionally, BOLD MRI has been reported in IRI-AKI and CI-AKI models [ 69 , 94 , 95 ]. Hofmann et al [ 96 ] reported that post-AKI changes in R 2 * values were induced by several drugs, including indomethacin, radio-contrast media, cyclosporine, and tacrolimus.…”
Section: Basic Imaging Approaches For Akimentioning
confidence: 99%
“…Insights into renal oxygenation can be derived from blood oxygenation level–dependent (BOLD) MRI, which offers a non‐invasive in vivo technique . Renal BOLD‐MRI methodology has progressed and a large body of literature on (pre)clinical applications is available. The growing number of reports eloquently speaking about renal BOLD‐MRI and the consensus papers on technical recommendations document the value of non‐invasive MRI to renal (patho)physiology.…”
Section: Introductionmentioning
confidence: 99%